Experimental and numerical investigation of anisotropic and twinning behavior in Mg alloy under uniaxial tension. (15th May 2016) - Guo, Xiaoqian; Chapuis, Adrien; Wu, Peidong; Liu, Qing; Mao, Xianbiao
Abstract: In plane tension of magnesium alloy sheets is accommodated by prismatic and basal slip, whereas 10 − 12 twinning is activated when grains are elongated along the < c > axis. The plastic behavior of Mg-3Al-1Zn in tension has been investigated using a thick rolled plate with a strong basal texture. Tensile tests were performed along five directions distributed between the normal direction and the transverse direction, allowing various amount of 10–12 twinning, basal, and prismatic slip to take place. The twinning behavior has been investigated using EBSD measurement and EVPSC modeling, and Schmid factor analysis was performed. The observed amount of variants with a Schmid factor of high rank is higher than predicted, emphasizing the necessity of strain accommodation between grains and twins. Compared with compression, even when twinning activity is low, more 10–12 twin variants are predicted in tension. This study confirms extension twinning as a major deformation mechanism in all tensile directions and an efficient way to harden Mg alloys by twin-twin boundaries. Graphical abstract: Highlights: EVPSC-TDT simulations of the mechanical behavior in ND-TD plane of a magnesium alloy AZ31 thick rolled plate in tension 10–12 twinning is activated and investigated in tension along different directions. 10–11 twinning is also included in the EVPSC-TDT model for the first time. More 10–12 twin variants of low Schmid factor are observed than predicted. More 10–12 variants are predicted in tension than in compression.